2021
DOI: 10.1007/s42322-021-00084-9
|View full text |Cite
|
Sign up to set email alerts
|

We love them anyway: outdoor environmental education programs from the accompanying teachers’ perspective

Abstract: The ways in which residential outdoor environmental education programs are perceived by the teachers accompanying their elementary school students have rarely been investigated. In this study, interviews were conducted with 17 elementary school teachers who had participated in one of five selected residential programs in the Czech Republic in 2018 – 2019. As the findings show, all the teachers found the residential programs beneficial for their teaching. However, a majority of the teachers reported that the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
1
4
0
1
Order By: Relevance
“…This study further supports the crucial relationship between the program characteristics, students' values, and program effects. As found in a previous study (Johnson & Cincera, 2021), students with more pro-environmental values tend to rate the program's instructional strategies more highly than do students holding more anthropocentric values. This relationship works for environmental values before the program and even more so after the program.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This study further supports the crucial relationship between the program characteristics, students' values, and program effects. As found in a previous study (Johnson & Cincera, 2021), students with more pro-environmental values tend to rate the program's instructional strategies more highly than do students holding more anthropocentric values. This relationship works for environmental values before the program and even more so after the program.…”
Section: Discussionsupporting
confidence: 67%
“…In both pretest and posttest, we used the 2-MEV scale for measuring students' environmental values of nature preservation, utilization of nature, and appreciation of nature (Bogner, 2018). The instrument's composition and reliability are carefully described in Johnson and Cincera (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the results revealed that the instrument meets the necessary psychometric requirements and can be considered a valid and reliable instrument for measuring teachers' environmental literacy levels. This research also revealed interesting results regarding the relationship between teachers' EL levels and their educational areas, accompanying learning area engagement, and environmental education training in general (An et al, 2022;Cincera et al, 2021). In this regard, an Environmental Literacy Instrument based on Spirituality (ELIS) has been developed (Husamah et al, 2022), in the Indonesian context.…”
Section: Introductionmentioning
confidence: 89%